2021
DOI: 10.1088/1741-4326/ac3be5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the microtearing modes in the pedestal of DIII-D H-modes using gyrokinetic simulations

Abstract: Recent evidence points toward the microtearing mode (MTM) as an important fluctuation in the H-mode pedestal for anomalous electron heat transport. A study of the instabilities in the pedestal region carried out using gyrokinetic simulations to model an ELMy H-mode DIII-D discharge (USN configuration, 1.4 MA plasma current, and 3 MW heating power) is presented. The simulations produce MTMs, identified by predominantly electromagnetic heat flux, small particle flux, and a substantial degree of tearing parity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 36 publications
6
33
0
Order By: Relevance
“…Such variations in MTM physics appear to be responsible for the multiple bands that are observed in some discharges. For example, DIII-D discharge 162940 exhibits three distinct frequency bands: narrow bands at 40 kHz, 80 kHz, and a broader band centered at 400 kHz, which are in quantitative agreement with simulations as described in reference [41].…”
Section: Simple Mtm Dispersion Relationsupporting
confidence: 88%
“…Such variations in MTM physics appear to be responsible for the multiple bands that are observed in some discharges. For example, DIII-D discharge 162940 exhibits three distinct frequency bands: narrow bands at 40 kHz, 80 kHz, and a broader band centered at 400 kHz, which are in quantitative agreement with simulations as described in reference [41].…”
Section: Simple Mtm Dispersion Relationsupporting
confidence: 88%
“…On JET, detailed comparisons with gyrokinetic simulations showed that experimentally-observed frequency bands in magnetic fluctuations were consistent with expectations from MTMs and that MTM fluctuations produce experimentally-relevant transport [25]. Additional ongoing work at DIII-D [27,28] and elsewhere is continuing to support the notion that MTMs are present in the H-mode pedestal, perhaps alongside additional instabilities.…”
Section: Introductionsupporting
confidence: 53%
“…In particular, models based off of KBM constraints have been extensively developed and are able to reproduce observed pedestal heights and widths to within ∼ 20% on many machines [6,7]. However, ongoing gyrokinetic work has suggested that other modes, especially the MTM [9][10][11][12], may also contribute to transport mechanisms in the pedestal region, potentially having large effects on energy regulation [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…On the longer timescale of the electron temperature gradient (ETG) recovery, the TEM turbulence (figure 7(b)) exhibits a threshold in ETG (figure 7(c)) and then saturates later in the ELM recovery. MTM scale electro-magnetic modes (figure 7(d)) driven by grad-T e can also contribute to the anomalous Q e through to the end of the ELM cycle as suggested by non-linear simulations [32][33][34], although their experimental identification is not yet conclusive in this set of experiments. Finally, simulations predict that ETG modes also contribute to Q e between ELMs [36], although the spatial scales are so short that no direct measurements of ETG scale fluctuations in the pedestal are available.…”
Section: Fundamental Plasma Physics Understanding and Model Validatio...mentioning
confidence: 82%